PEMBERDAYAAN REMAJA KARANGTARUNA RT 7 RW 9 KELURAHAN GEMAH KOTA SEMARANG MELALUI PELATIHAN KETERAMPILAN MEMBATIK - Muhtarom Muhtarom; Muhammad Saifuddin Zuhri; Duwi Nuvitalia; Bambang Agus Herlambang; Ernawati Saptaningrum (Universitas PGRI Yogyakarta, 2021)
Batik training given for youth Karangtaruna RT 7 RW 9 Gemah, Pedurungan, Semarang City to improve their knowledge and skills in opening opportunities for entrepreneurship. The method used to achieve this goal is by training more demonstrations, question and answer and practice as well as mentoring. The training material is presented with more practice than theory, with a ratio of 25% theory and 75% practice. The results of the training show that youth Karangtaruna RT 7 RW 9 Gemah, Pedurungan, Semarang City have an understanding and skills in batik cap, namely: knowledge of batik and entrepreneurship, the process of stamping batik and mending motifs, the batik coloring process, the fixation process, the pelorodan process, and finishing. Participants who previously did not know the technique of making batik understood and were able to practice the batik process. This is shown by the work produced by the community service participants.